2018
DOI: 10.1096/fj.201701557r
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine programming mechanism for hypercholesterolemia in prenatal caffeine‐exposed female adult rat offspring

Abstract: Clinical and animal studies have indicated that hypercholesterolemia and its associated diseases have intrauterine developmental origins. Our previous studies showed that prenatal caffeine exposure (PCE) led to fetal overexposure to maternal glucocorticoids (GCs) and increased serum total cholesterol levels in adult rat offspring. This study further confirms the intrauterine programming of PCE-induced hypercholesterolemia in female adult rat offspring. Pregnant Wistar rats were intragastrically administered ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…Based on our and other precious studies, liver modulates cholesterol transport, biosynthesis and transformation in pigs predominantly via epigenetic regulation (20,21). We chose CYP7a1 and HMGCR for epigenetic because the promoter sequences of these two genes can be used in pigs and both of them are key enzymes in the cholesterol metabolism (20,29,30). CpG island cytosine methylation located in promoter genes is associated with gene suppression (31,32), while histone acetylation is related to the activation of transcription (20,29,30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on our and other precious studies, liver modulates cholesterol transport, biosynthesis and transformation in pigs predominantly via epigenetic regulation (20,21). We chose CYP7a1 and HMGCR for epigenetic because the promoter sequences of these two genes can be used in pigs and both of them are key enzymes in the cholesterol metabolism (20,29,30). CpG island cytosine methylation located in promoter genes is associated with gene suppression (31,32), while histone acetylation is related to the activation of transcription (20,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…We chose CYP7a1 and HMGCR for epigenetic because the promoter sequences of these two genes can be used in pigs and both of them are key enzymes in the cholesterol metabolism (20,29,30). CpG island cytosine methylation located in promoter genes is associated with gene suppression (31,32), while histone acetylation is related to the activation of transcription (20,29,30). According to the type of histone, the position of amino acid residues and the number of methyl groups (mono-, di-and trimethylation), histone methylation can inhibit or activate gene transcription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistically, the adverse effects of caffeine on F1 offspring could be due to early embryo caffeine exposure via oviductal or uterine fluid [15], or during later exposure that bypasses the blood-placenta barrier. In addition to the direct effect of caffeine exposure, recent studies also found that caffeine intake during mid-to-late pregnancy can cause an increase in maternal glucocorticoids [56]; fetus exposed to such an environment can result in long-term programming of fetal hypothalamic-pituitary-adrenal axis [57], which could disrupt neuroendocrine metabolism and increase susceptibility to metabolism syndrome, such as hypercholesterolemia, in adult offspring [56,58] (Figure 3).…”
Section: Prenatal Caffeine Exposure: Significance To the Long-term Hementioning
confidence: 99%
“…Whereas, caffeine exposure during pregnancy can do a variety of short‐term and long‐term harm to offspring. In our previous studies, we found that prenatal caffeine exposure caused developmental toxicities of multiple organs in fetal offspring and susceptibility to several kinds of diseases in adulthood (He et al, 2019; Shangguan et al, 2017; Tan et al, 2012; Xu et al, 2018). However, the effects of prenatal caffeine exposure on peak bone mass accumulation and osteoporosis susceptibility in offspring and the underlying mechanism have not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%